Management of Non-response and Loss of Response to Anti-tumor Necrosis Factor Therapy in Inflammatory Bowel Disease - Marsal, Jan; Barreiro-de Acosta, Manuel; Blumenstein, Irina; Cappello, Maria; Bazin, Thomas; Sebastian, Shaji (Frontiers in Medicine, 2022)
Anti-TNF therapy has been successfully used as first-line biologic treatment for moderate-to-severe inflammatory bowel disease (IBD), in both ‘step-up’ and ‘top-down’ approaches, and has become a cornerstone of IBD management. However, in a proportion of patients the effectiveness of anti-TNF therapy is sub-optimal. Either patients do not achieve adequate initial response (primary non-response) or they lose response after initial success (loss of response). Therapeutic drug monitoring determines drug serum concentrations and the presence of anti-drug antibodies (ADAbs) and can help guide treatment optimization to improve patient outcomes. For patients with low drug concentrations who are ADAb-negative or display low levels of ADAbs, dose escalation is recommended. Should response remain unchanged following dose optimization the question whether to switch within class (anti-TNF) or out of class (different mechanism of action) arises. If ADAb levels are high and the patient has previously benefited from anti-TNF therapy, then switching within class is a viable option as ADAbs are molecule specific. Addition of an immunomodulator may lead to a decrease in ADAbs and a regaining of response in a proportion of patients. If a patient does not achieve a robust therapeutic response with an initial anti-TNF despite adequate drug levels, then switching out of class is appropriate. In conjunction with the guidance above, other factors including patient preference, age, comorbidities, disease phenotype, extra-intestinal manifestations and treatment costs need to be factored into the treatment decision. In this review we discuss current evidence in this field and provide guidance on therapeutic decision-making in clinical situations.